Slovensko slovaropisje in kritika - Merše, Majda (Slavia Centralis, 2020)
SLOVENE LEXICOGRAPHY AND CRITIQUE A parallel phenomenon to Slovene lexicography has been its critique, which has been brought to the fore only in the past two centuries. Lexicographic works of a general nature received the most signifcant critical response, i. e., the Slovar slovenskega knjižnega jezika [Dictionaryof Standard Slovene] (1970–1991) and Slovenski pravopis [Slovene Orthography] (2001). The article presents the scope of lexicographic critique, its typology and impact, as well as the main critical issues, along with some sample material.